Evaluation of vertical dimension before and after insertion of removable dentures: Study observasional - Damayanti, Lisda; Fuadi, Muhamad Firdaus; Wulansari, Daisy (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2025)
ABSTRACTIntroduction: Dentures play a role in returning both physiological function and esthetics of a patient that experiences tooth loss, one of the steps in denture fabrication is vertical dimension measurements that consists of the Vertical Dimension of Occlusion (VDO) and the Vertical Dimension at Rest (VDR), this step is crucial in ensuring the rehabilitation of function and esthetics are achieved. The purpose of this study is to analyze the suitability of vertical dimension measurements before and after insertion of complete dentures. Methods: This is an observational study using the cross sectional method done on 30 patients indicated for removable dentures treated by coassistents and residency at prosthodontic clinic RSGM UNPAD. Sample size is determined using the purposive sampling method. Measurements are done using the 2 dot method, first measurements are done prior to insertion using the Niswonger method which is VDR subtracted by freeway space to get the first VDO measurement. The second measurement is done after denture insertion which then patients are put in the centric occlusion position, the distance between the 2 dots subnation and gnation are measured to get the second VDO after insertion Results: Probability value of p=0,000 using paired t-test analysis shows that there is significant difference between VDO and DVF before and after insertion off dentures (p-value 0,000 ≤0,05). Conclusion: There is a difference in the measurement of the VDO between before and after the insertion of complete removable dentures, and this difference remains within an acceptable tolerance range.KEY WORDS: complete dentures, vertical Dimension of Occlusion, physiologic vertical dimension, before and after denture insertionEvaluasi pengukuran dimensi vertikal sebelum dan sesudah pemasangan gigi tiruan lengkap lepasan: Studi observasionalABSTRAKPendahuluan: Langkah penting pada rehabilitasi gigi tiruan yang berperan untuk mengembalikan fungsi dan estetik dari pasien yang kehilangan gigi adalah pengukuran dimensi vertikal yang terbagi menjadi Dimensi Vertikal Oklusi (DVO) dan Dimensi Vertikal Fisiologis (DVF). Tujuan dari penelitian ini adalah untuk menganalisis kesesuaian dimensi vertikal sebelum dan sesudah pemasangan gigi tiruan lengkap lepasan. Metode: Jenis penelitian ini merupakan metode observasional dengan desain cross sectional. Subjek pasien poliklinik Prostodonsia RSGM UNPAD. Data dimensi vertikal oklusi pasien sebelum pemasangan gigi tiruan (diukur dengan rumus Niswonger, DVO= DVF-2 mm freeway space pada posisi istirahat fisiologis) dan sesudah pemasangan gigi tiruan saat oklusi sentrik, diukur dengan mengukur jarak 2 titik subnation dan gnation. Hasil: Hasil nilai probabilitas p=0,000 menggunakan uji paired t-test menunjukan terdapat perbedaan yang signifikan pada pengukuran DVF dan DVO sebelum dan sesudah pemasangan gigi tiruan lengkap lepasan (p-value 0,000 ≤0,05). Simpulan: Terdapat perbedaan hasil pengukuran Dimensi Vertikal Oklusi (DVO) antara sebelum dan sesudah pemasangan gigi tiruan lengkap lepasan, tetapi perbedaan hasil ini masih dalam batas toleransi yang dapat diterima.KATA KUNCI: Gigi Tiruan Lengkap Lepasan, dimensi Vertikal oklusi, dimensi vertikal fisiologis, sebelum dan sesudah pemasangan gigi tiruan